Precizno mjerenje izmjenične struje Rogowskijevim svitkom : doktorska disertacija - Ferković, Luka (L. Ferković ; Fakultet elektrotehnike i računarstva, 2007)
This thesis covers the elaboration of non-dissipative method of the AC current measurement by air core current transformer based on Rogowski coil. Since the accuracy of AC current measurement achieved by this transducer depends primarily on mutual inductance of coil and current conductor, the special attention is payed to the analytical methods, wich consider many influence quantities. Moreover, their experimental verifications are performed on models developed especially for this purpose. The coil output voltage is proportional to the rate of change of the current being measured and since the voltage is very small (typically a few milivolts) at the low frequencies, the use of the electronic integrator is required, which also assures linearity of the transducer transimpedance in frequency domain. Because of low sensitivity of the transformer, the problem with superimposed disturbances may appear. This is solved by special double astatic secondary windings and specific symmetrical integrator with the balanced inputs and instrumentation amplifier on its output. The temperature stabilisation of the transformer is achieved by its placing into the sealed cylinder, and use of compensation load, while the temperature drift of capacitances of integrator condensers is being neutralized by copper thermistor, which has influence on amplification of the circuit. The sensitivity of the transducer, established by calibration, is 0,179 V/A, and enable the measurement of current in range of 0,1 A to 15 A, from 20 Hz to 1 kHz. In this frequency band, by application of supreme digital voltmeters with 81 digits, the coil voltage measuring uncertainty of 7•10-5 is achieved. Moreover, the measuring uncertainty of transducer transimpedance is 2•10-4, partially because of the additional uncertainty of current. The performed experimental measurements point to the perspectivity of this measurement method, and show very good agreement to calculations. Therefore, by minor changes of the electronic part of the transducer and applying the alternative methods of transducer calibration during the further testings, the possibility of measurement of higher AC current with smaller uncertainty are expected. Key words: ac current measurement, nondissipative method, current transformer, Rogowski coil, mutual inductance, double astatic secondary windings, analitical methods of error determination, electronic integrator, digital multimeter,